von dürer bis gropius : Aufsätze zur deutschen Kunst - Grote, Ludwig (München : Prestel Verlag, 1975)
Dürer, Albrecht ; Stoss, Veit ; Grünewald, Matthias ; von Sandrart, Joachim ; Friedrich, Casper David ; Kandinsky, Wassily ; Klee, Paul ; Gropius, Walter ; etc.
boek
Keywords: Duitsland